Levels of serum lithium in manic depressive patients with mild persistent bronchial asthma - Chatterjee, Subhramay; Chakraborti, Sandip (International Journal of Research in Medical Sciences, 2020)
Background: Lithium, widely used in manic depressive (MD) patients, might protect the airways against constrictor stimuli in bronchial asthma (BA), through its effects on cell signal transduction and ion transport pathways. Methods: Serum lithium levels were studied in MD patients with better controlled mild persistent BA (group A) and MD patients with not so well controlled BA (group B). Results: Serum lithium levels were highly significantly more in group A compared to lithium levels in group B. Conclusions: Lithium may inhibit the contractile response of airway smooth muscle and can be used in treatment / monitoring of BA.